Case report: Rethinking NGS analysis in diagnosing Diamond-Blackfan anemia syndrome - Papasavva, Panayiota L.; Kaouranis, Konstantinos; Byrou, Stefania; Constantinou, Constantina G.; Efrosini, Iacovou; Kleanthous, Marina; Lederer, Carsten W.; Papasavva, Thessalia (Frontiers in Genetics, 2024)
Diamond-Blackfan anemia syndrome (DBAS) is a rare inherited bone marrow failure (BMF) syndrome characterized by erythroid aplasia, congenital malformations, and cancer predisposition. With its genetic heterogeneity, variable penetrance and expressivity, DBAS poses significant diagnostic challenges, necessitating advancements in genetic testing for improved accuracy. Here, we present the case of an 18-year-old male with a long-standing macrocytic anemia that remained undiagnosed despite standard whole exome sequencing (WES). Revisiting a family-trio WES analysis with clinical insight led to the identification of a likely pathogenic variant in the Ribosomal Protein S17 (RPS17) gene, previously masked due to analytical challenges and conservative filter settings. This variant, an initiation codon mutation, was confirmed in heterozygosity in both the proband and his mother through Sanger sequencing. Comprehensive imaging studies showed no malformations or organ anomalies in either individual, except for mild esophageal stenosis observed in both. RPS17 mutations, particularly those involving the initiation codon, have previously been linked to the DBAS phenotype, however due to analytical complexities involved in RPS17 sequencing analysis, strong pathogenic associations have not yet been firmly established. Our case warns of potential underdiagnosis of RPS17 variants in DBAS, highlighting the importance of clinical context and interdisciplinary collaboration in interpreting WES data to avoid false-negative results.